Cultural dynamics and tensions when applying design thinking for improving health-care quality. Issue 1 (5th January 2021) - Boström, Jonas; Hillborg, Helene; Lilja, Johan
Abstract : Purpose: The purpose of this paper is to contribute knowledge concerning the dynamics and potential cultural tensions that occur when applying user involvement and design thinking (DT) for improving quality in a health-care setting. Design/methodology/approach: This paper is based on a case study following a quality improvement (QI) project in a medium-sized Swedish county council in the field of somatic care. The project involved eight health-care professionals, one designer, four patients and two relatives. A multiple data collection method over a period of ten months was used. It included individual interviews, e-mail correspondence and observations of workshops that covered the QI project. Findings: The result shows tensions between QI work and the daily clinical work of the participants. These tensions primarily concern the conflict between fast and slow processes, the problem of moving between different fields of knowledge, being a resource for the individual clinic and the system and the participants' expectations and assumptions about roles and responsibilities in a QI project. Furthermore, these findings could be interpreted as signs of a development culture in the health-care context. Practical implications: There are several practical implications. Among others, the insights can inspire how to approach and contextualize the current concepts, roles and methods of DT and user involvement so that they can be more easily understood and integrated into the existing culture and way of working in the health-care sector. Originality/value: This study provides a unique insight into a case, trying to uncover what actually is going on and perhaps, why certain things are not happening at all, when user involvement and design practices are applied for improving health-care quality.